The Evaluation on Three Types of Malaysian Dolomites as a Primary Catalyst in Gasification Reaction of EFB and Tar Cracking Efficiency - Mohammed, M. A. A.; Shafizah, I. Nor; Salmiaton, A.; Wan Azlina, W. A. K. G.; Taufiq-Yap, Y. H. (Frontiers in Energy Research, 2020)
The conversion of biomass into hydrogen-rich syngas has been getting attention recently, as it has potential sustainability benefits of agricultural residues. In this study, gasification of empty fruit bunch (EFB) was performed using various calcined Malaysian dolomite catalysts, which were denoted as P1, P2, and P3. The physicochemical properties of the catalysts were examined using X-ray fluorescence (XRF), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), and scanning electron microscopy (SEM). The effect of various catalyst to biomass (C/B) ratios (varied in the range of 0.05–0.3 in an increment of 0.05) of P1, P2, and P3 catalyst in EFB gasification was evaluated at a gasifier temperature of 850°C. The gas produced was analyzed by gas chromatography (GC). The effect of various C/B ratios on tar conversion was also examined. The result showed that, with lower impurities in calcined dolomites and high content of active sites (CaO–MgO), improved characteristics of P1 and P2 in crystalline structure contributes to a significant reduction in tar cracking ( 78 and 75%, respectively) and higher H2 yield (32.25 mg H2/g EFB).